A versatile synthetic route for the preparation of titanium metal–organic frameworks. Issue 2 (11th November 2015) - Zou, Lanfang; Feng, Dawei; Liu, Tian-Fu; Chen, Ying-Pin; Yuan, Shuai; Wang, Kecheng; Wang, Xuan; Fordham, Stephen; Zhou, Hong-Cai
Abstract : Through a versatile synthetic strategy, High Valence Metathesis and Oxidation (HVMO), a series of Ti-MOFs with predesigned topologies and structures were synthesized. Abstract : Exploitation of new titanium metal–organic frameworks (Ti-MOFs) with high crystallinity has been attracting great attention due to their vast application potential in photocatalysis. Herein a versatile synthetic strategy, namely, High Valence Metathesis and Oxidation (HVMO), is developed to synthesize a series of Ti-MOFs with predesigned topologies and structures. The crystallinity of these Ti-MOFs was well maintained throughout, as confirmed by powder X-ray diffraction and gas adsorption measurements. Significantly, there were only a few examples of Ti-MOFs, not to mention a general synthetic strategy for various kinds of Ti-MOFs in the literature. This contribution also illustrates the intriguing potential of Ti-MOF platforms in photocatalysis.